1981
DOI: 10.1128/iai.32.1.24-27.1981
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of the lymphoproliferative response to varicella-zoster virus antigen in the aged

Abstract: Humoral antibodies and specific cellular immune reactions (proliferative immune response in the lymphocyte transformation test) to varicella-zoster virus antigen were measured in children, young adults, and elderly people. In children and young adults, the humoral varicella-zoster-specific antibodies and the virusspecific cellular immune response generally coincided. In the over-60 age group, however, a discrepancy was often observed between these parameters. Ninety percent of the elderly subjects showed humor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(38 citation statements)
references
References 17 publications
1
37
0
Order By: Relevance
“…Moreover, VZV reactivation involves spread of virus throughout the tissue and can be altered by cellular as well as humoral immune responses. This could explain why the incidence of zoster increases with age, since it has been shown that VZV-specific T-cell responses diminish with advancing age (Miller 1980, Berger et al 1981, and why zoster is so prevalent in immune-compromised individuals. This also explains the meningeal reaction with cerebrospinal fluid pleocytosis due to the active infectious process.…”
Section: A Model Of Hsv and Vzv Latent Infections And Reactivationsmentioning
confidence: 99%
“…Moreover, VZV reactivation involves spread of virus throughout the tissue and can be altered by cellular as well as humoral immune responses. This could explain why the incidence of zoster increases with age, since it has been shown that VZV-specific T-cell responses diminish with advancing age (Miller 1980, Berger et al 1981, and why zoster is so prevalent in immune-compromised individuals. This also explains the meningeal reaction with cerebrospinal fluid pleocytosis due to the active infectious process.…”
Section: A Model Of Hsv and Vzv Latent Infections And Reactivationsmentioning
confidence: 99%
“…responses in these varicella patients were the mean patient age was 34 years [Bovill and Bannister, 1998]. The low responses obtained with zoster patients may again be a reflection of age and waning immunocompetence [Berger et al, 1981].…”
Section: Discussionmentioning
confidence: 93%
“…The pathogenesis of reactivation of VZV following primary chickenpox has not as yet been established. Antibodies levels (including VZV-specific IgA) are maintained at normal or sometimes even raised levels in elderly and immunocompromised individuals [Miller, 1980;Gershon and Steinberg, 1981;Burke et al, 1982;Berger et al, 1981;Levy et al, 19831. However, diminished cellular immune function manifesting as reduced in-vivo skin test and in-vitro lymphoproliferative responses to VZV antigen have been demonstrated in the aged and are presumed to be related to increased incidence of zoster in elderly and immunocompromised individuals [Miller, 1980;Gershon and Steinberg, 1981;Burke et al, 1982;Berger et al, 1981 I.…”
Section: Discussionmentioning
confidence: 99%